PENGARUH MEDIA SOSIAL TERHADAP PERUBAHAN DAN PERGESERAN MAKNA BAHASA INDONESIA DI KALANGAN ANAK MUDA - Bunga Lisa Fitriani; Lira Fathna Hamida; Nadia Clara Angelina; Nisa Fitri Fuadah; Nurisa Najla Aqilah; Rama Wijaya Abdul Rozak (JURNAL SKRIPTA, 2026)
The massive use of social media among young Indonesians has influenced the development of the Indonesian language, particularly in terms of rapid and often unnoticed changes and shifts in word meaning. This study aims to identify the factors driving changes and semantic shifts in language among young users, identify the use of slang and language variations that emerge in adolescent communication on social media, and analyze the influence of social media language use on everyday Indonesian language use. This study employed a quantitative method with data collected through an online questionnaire distributed to 159 respondents under the age of 21 who actively use TikTok, Instagram, and Twitter/X. The questionnaire was developed using a four-point Likert scale and multiple-choice questions. The collected data were then analyzed descriptively in the form of frequency and percentage. The results show that 87.4% of respondents frequently use viral terms from social media; 79.2% are aware of semantic shifts in those words; TikTok was the most influential platform shaping respondents' language style (84.9%); mixed Indonesian-foreign language dominated digital communication (86.2%); and viral content (66%) and peer influence (60.4%) were the main factors driving language change. It is concluded that social media serves as a significant agent of semantic change in the Indonesian language and potentially weakens the formal language proficiency of younger generations if not accompanied by proper and sustainable language development efforts.